Analisis Perkembangan Sosial Emosional Anak pada Usia 3-4 Tahun - Rafika, Nurmaya; Sit, Masganti (Darul Yasin Al Sys, 2024)
This study aims to gain an in-depth understanding of the social-emotional development of children aged 3-4 years. A qualitative descriptive approach was used to explore social interactions, emotional regulation, and language development of children in their everyday contexts. The research methods involved direct observation, interviews with parents, and participatory observations during children's play activities. The collected data were analyzed using a thematic approach to identify patterns and key themes. The findings of the study revealed that children aged 3-4 years show a growing interest in interacting with peers. They begin to learn simple rules of group play and demonstrate the ability to share toys. Children's language skills also undergo significant development, as they are able to use longer and more complex sentences and express their feelings and thoughts through words. Furthermore, children at this age start developing self-awareness, recognizing their own identities, and understanding their roles within a group. They also begin to learn emotional regulation, although they may still struggle with controlling rapid mood changes. The capacity for empathy also begins to develop, as children show concern for injured or sad peers. This study provides a deeper understanding of the social-emotional development of children aged 3-4 years. The implications of these findings can inform early childhood education and care approaches, emphasizing the importance of positive social interactions, healthy emotional regulation, and the development of empathy skills during this period.